Enhancing Janti Park's Marketing Strategy through Human Resources Digital Training - Sri Tomo; Didik Nugroho; Arie Febrianto; Aninda Dyah Hayu Pinasti Putri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This Community Service Activity aims to strengthen the digital marketing strategy of Janti Park Tourism Park, Klaten, which faces stiff competition from similar water tourism destinations, by improving human resource capabilities in visual content production. The method used is training and hands-on practice carried out in three main stages: mentoring icon design, producing a snowman as an official icon, technical training in video shooting and editing, and graphic design training, this activity culminates with mentoring in creating promotional video content. The main results of this community service activity are the formation of a new digital marketing team skilled in producing ready-to-upload content, as well as a drastic increase in the frequency of promotional content posting on social media. Before the training, uploads were made on average once every two weeks or 2–3 times per month. After the training and mentoring, the posting frequency increased sharply to once every two days, or around 15–16 pieces of content per month, which indicates significant social media optimization and improved digital marketing performance to strengthen Janti Park's branding and visibility.